Stancing solidarity: Twitter communication in Qatar during the blockade - Irene Theodoropoulou (18094816) (2025)
This paper deals with the sociolinguistically under-theorized concept of solidarity in the context of Twitter-based communication during the blockade that was imposed on Qatar from June 2017 until January 2021. The data collected for this project include a sociolinguistic corpus from Twitter, which has been analyzed in the context of linguistic ethnography. Instead of providing an broad or overarching definition of solidarity, we argue for a close and context-rich approach to the concept based on textual analysis. In particular, we show that solidarity is realized as an online sociolinguistic act of religious, psychological, cultural, social, and grass roots political stance in the context of a heterogeneous community through new ways of textually configuring political relations. The latter translate into the collapsing of traditional binaries found in this absolute monarchical context, such as hatharis (“urban”) and bedouin (“nomads”), or Qataris and non-Qataris, and hierarchies, such as the ruling family and the rest of the people, who live and work in Qatar. In terms of its more practical implications, this paper can be seen as a guide for the Qatari government to develop strategies in strengthening internal solidarity and resilience against any potential future crises. Other Information Published in: Humanities and Social Sciences Communications License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: https://dx.doi.org/10.1057/s41599-025-04420-y